2022
DOI: 10.1002/ana.26354
|View full text |Cite
|
Sign up to set email alerts
|

Tmax Volumes Predict Final Infarct Size and Functional Outcome in Ischemic Stroke Patients Receiving Endovascular Treatment

Abstract: The objective of this paper was to explore the utility of time to maximum concentration (T max )-based target mismatch on computed tomography perfusion (CTP) in predicting radiological and clinical outcomes in patients with acute ischemic stroke (AIS) with anterior circulation large vessel occlusion (LVO) selected for endovascular treatment (EVT). Methods: Patients with AIS underwent CTP within 24 hours from onset followed by EVT. Critically hypoperfused tissue and ischemic core volumes were automatically calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Comparisons with postinterventional CT/ magnetic resonance imaging data are needed to validate the accuracy of the lesion delineation and the evaluation of alternative CTP-based core lesion definitions. 44 Third, mRS represents a parameter of global disability that lacks to detect domain-specific (eg, motor) deficits and alterations. 45 Using more complex outcome parameters reflecting deficits in motor, language, and attention, and their impact on functional independence most likely will help to identify the most relevant neuroanatomical structures for functional outcome after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons with postinterventional CT/ magnetic resonance imaging data are needed to validate the accuracy of the lesion delineation and the evaluation of alternative CTP-based core lesion definitions. 44 Third, mRS represents a parameter of global disability that lacks to detect domain-specific (eg, motor) deficits and alterations. 45 Using more complex outcome parameters reflecting deficits in motor, language, and attention, and their impact on functional independence most likely will help to identify the most relevant neuroanatomical structures for functional outcome after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…7 Prognostic perfusion imaging parameters included relative cerebral blood flow (rCBF) <30%, time to maximum (Tmax) volumes, the hypoperfusion intensity ratio, the mismatch profile, and the cerebral blood volume (CBV) index. [8][9][10][11][12] In AIS patients with anterior circulation occlusions, it has been shown that the presence of collaterals is another important predictor of radiologic and clinical outcome. 13 These findings indicate that imaging parameters may be excellent prognostic indicators for patients with AIS.…”
Section: Al Found That Althoughmentioning
confidence: 99%
“…8 A threshold for the time to peak of the residue function (Tmax) exceeding 6 seconds has been identified as a reliable predictor for tissues at risk of infarction if there is no reperfusion. 9 However, the extent to which different software solutions can be used interchangeably, especially in terms of their clinical significance for planning treatment and estimating prognosis, remains uncertain. Previous research has indicated significant discrepancies in the calculated volumes of the ischemic core across different software, leading to inconsistent predictions of final infarct volume after mechanical thrombectomy.…”
Section: Introductionmentioning
confidence: 99%